+0  
 
0
307
2
avatar

Pouvez-vous résoudre ce avec le calcul étapes 2x ^ 2 + x-6 = 4x ^ 2-4x-3

Guest Apr 15, 2017
 #1
avatar
0

Solve for x:
2 x^2 + x - 6 = 4 x^2 - 4 x - 3

Subtract 4 x^2 - 4 x - 3 from both sides:
-2 x^2 + 5 x - 3 = 0

The left hand side factors into a product with three terms:
-(x - 1) (2 x - 3) = 0

Multiply both sides by -1:
(x - 1) (2 x - 3) = 0

Split into two equations:
x - 1 = 0 or 2 x - 3 = 0

Add 1 to both sides:
x = 1 or 2 x - 3 = 0

Add 3 to both sides:
x = 1 or 2 x = 3

Divide both sides by 2:
Answer: | x = 1                   or                    x = 3/2

Guest Apr 15, 2017
 #2
avatar+280 
0

 

 

x= 1 , x= 3/2. 

 

Utiliser la formule quadratique

Veteran  Apr 15, 2017
edited by Veteran  Apr 15, 2017

31 Online Users

avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.